IS THE NATIONAL PENSION SYSTEM AS PROMISING AS THE OLD PENSION SYSTEM IN TERMS OF BENEFICIARIES' INTEREST IN INDIA: A COMPARATIVE ANALYSIS - Aggarwal, Shruti; Khanna, Ashu; Kumar, Pratyush (The journal of contemporary issues in business and government, 2023)
The major revolution came in India's social security and pension sector when the old pension system was replaced by the defined contribution, the new pension system, now called the National pension system. The new system created havoc and induced apprehension and dubiety in Government employees regarding their future benefits. This study attempts to determine whether the National pension system is a cause to worry for employees or is it just a fear of the unknown. A comparison is attempted between both old and new pension systems to gauge if there is a remarkable difference in benefits. Among the variables considered, it is found that the ROI and age of entry into the job exert the most influence on the pension amount. The other two variables, Government contribution rate and job level, have less impact. A case is formed by changing the allocation rate in pension and lumpsum fund to 50:50, which is currently 60:40. A change in allocation rate also positively impacts the pension amount, which is one of the study's implications. The study's outcome benefits the government, the investors and fund managers as they can imply them to make the new system more attractive and make the benefits at par with the old system.